2022
DOI: 10.3390/cells11040733
|View full text |Cite
|
Sign up to set email alerts
|

Early Cellular, Molecular, Morphological and Behavioral Changes in the Humanized Amyloid-Beta-Knock-In Mouse Model of Late-Onset Alzheimer’s Disease

Abstract: The purpose of our study is to investigate early cellular, molecular, morphological and behavioral changes in humanized amyloid-beta-knock-in (hAbKI) mice. Using seven-month-old homozygous hAbKI mice, we studied behavioral phenotype parameters, including spatial learning and memory (Morris Water Maze), locomotor activity (open field), working memory (Y-maze) and motor coordination (rotarod); mRNA abundance, protein levels, soluble amyloid-beta 40 and 42 levels and regional immunoreactivities of key markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…These and other observations [ 128 , 129 ] strongly suggest mitophagy enhancers are promising drugs to treat patients with AD and other tauopathies. However, these drugs need to be tested carefully using mouse models, particularly recently developed humanized Abeta knock-in (hAbKI) mice that express human amyloid beta peptide and exhibit late-onset AD features [ 130 , 131 ]. Currently, we are several mitophagy enhancers in late-onset hAbKI mice.…”
Section: Discussionmentioning
confidence: 99%
“…These and other observations [ 128 , 129 ] strongly suggest mitophagy enhancers are promising drugs to treat patients with AD and other tauopathies. However, these drugs need to be tested carefully using mouse models, particularly recently developed humanized Abeta knock-in (hAbKI) mice that express human amyloid beta peptide and exhibit late-onset AD features [ 130 , 131 ]. Currently, we are several mitophagy enhancers in late-onset hAbKI mice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent behavioral study of 7-month-old hAbKI mice revealed defects in motor coordination, locomotor activity, spatial and learning/working memory [ 41 ]. Our current study findings of the behavioral phenotype are improved in urolithin A and a combination of urolithin A+EGCG-treated hAbKI mice; however, protective effects are stronger in combination treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study of 7-month-old homozygous hAbKI mice revealed that hAbKI mice showed behavioral impairments in motor coordination, reduced locomotor and exploration activities, and impairments in working memory and spatial learning and memory [ 41 ]. The mRNA and protein analyses revealed the increased expression of mitochondrial fission genes and reduced expression of mitochondrial-fusion, mitochondrial biogenesis, synaptic, autophagy and mitophagy genes in hAbKI mice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations